1989
DOI: 10.1111/j.174-1617.1989.tb01294.x
|View full text |Cite
|
Sign up to set email alerts
|

Shared Parenting: Critical Review of the Research Literature

Abstract: This critical review of the shared parenting research literature highlights the need for sociolegal reform. This article was submitted to the Meyer Elkin Essay Contest and was selected for publication because of its quality and relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
(35 reference statements)
2
1
0
2
Order By: Relevance
“…Although many of the studies reviewed by Bauserman compared self-selected joint custody families with sole custody families, several included legally mandated joint physical custodial arrangements, where joint custody was ordered over the objections of the parents. These families fared as well as the selfselected samples, confirming the findings of earlier studies that joint custody works equally well for conflictual families in which parents are vying for custody (Benjamin and Irving, 1989;Brotsky et al, 1988). Bauserman also found that interparental cooperation increases over time in shared custody arrangements, and decreases in sole custody arrangements.…”
Section: A Rebuttable Legal Presumption Of Equal Parenting Responsibisupporting
confidence: 87%
See 1 more Smart Citation
“…Although many of the studies reviewed by Bauserman compared self-selected joint custody families with sole custody families, several included legally mandated joint physical custodial arrangements, where joint custody was ordered over the objections of the parents. These families fared as well as the selfselected samples, confirming the findings of earlier studies that joint custody works equally well for conflictual families in which parents are vying for custody (Benjamin and Irving, 1989;Brotsky et al, 1988). Bauserman also found that interparental cooperation increases over time in shared custody arrangements, and decreases in sole custody arrangements.…”
Section: A Rebuttable Legal Presumption Of Equal Parenting Responsibisupporting
confidence: 87%
“…Comparing child adjustment in joint physical and legal custody settings with sole custody, as well as intact family settings, and examining children's general adjustment, family relationships, self-esteem, emotional, and behavioral adjustment, divorce-specific adjustment, as well as the degree and nature of ongoing conflict between parents, Bauserman found that children in joint custody arrangements fare significantly better than those in sole custody on all measures. High conflict families fared as well as the self-selected samples, reinforcing the findings of earlier studies that joint custody works equally well for high conflict families in which parents are vying for custody (Benjamin and Irving, 1989;Brotsky, Steinman, and Zemmelman, 1988).…”
supporting
confidence: 83%
“…Beginning two decades ago, Johnston and colleagues (Johnston, 1995; Johnston, Kline, & Tschann, 1989) identified cautions against substantively shared parenting for children whose parents' ongoing acrimony and inability to encapsulate their conflict meant continued exposure to toxic inter‐personal dynamics and the diminished responsiveness of each parent. Others have identified elevated stress and anxiety for parents concerned about their child's well‐being in the care of the other parent, unwanted reduction of the maternal role, elevated conflict brought about by the frequent communication and decision making required in co‐parenting, and continuing abuse of power by controlling or violent ex‐spouses in that process (Benjamin & Irving, 1989; McKinnon & Wallerstein, 1986).…”
Section: Conflicting Guidance From the Research Literaturementioning
confidence: 99%
“…Er is een verband tussen de verblijfsregeling van kinderen en verschillende aspecten van het ouderlijke leven na een echtscheiding. Coouders vinden sneller een nieuwe partner en zijn meer tevreden over hun leven in het al-gemeen (Bauserman, 2012;Benjamin & Irving, 1989;Rothberg, 1983;Sodermans, Vanassche, & Matthijs, 2011). Co-vaders kunnen makkelijker een stabiele en duurzame relatie met hun kinderen onderhouden dan vaders die hun kinderen slechts een minderheid van de tijd zien (Bastaits, Ponnet & Mortelmans, 2012).…”
Section: Sociaal Levenunclassified
“…In vergelijking met alleenstaande ouders, zijn coouders de helft van de tijd 'kinderloos'. De tijd die vrijkomt door de zorgtaken te delen met de ex-partner kunnen ze benutten om deel te nemen aan sociale activiteiten buitenshuis en om hun netwerken te onderhouden (Benjamin & Irving, 1989). In vergelijking met nietresidentiële ouders blijven co-ouders nog steeds erg betrokken bij hun kinderen, wat ook hun sociale participatie in de hand kan werken (Ross, 1995).…”
Section: Sociaal Levenunclassified